EXPLORING THE IMPACT OF EMOTIONAL INTELLIGENCE AND LEADERSHIP STYLE ON ORGANIZATIONAL GROWTH: A STUDY OF KEY PERFORMANCE INDICATORS - Dhingra, Arti; Barkha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of emotional intelligence and leadership style on organizational growth, focusing on key performance indicators such as revenue growth, employee productivity, and satisfaction. As organizations increasingly recognize the value of emotionally intelligent leadership, understanding how emotional intelligence and effective leadership behaviours contribute to growth has become essential. The study employs a quantitative approach, using a structured questionnaire based on a 5-point Likert scale to measure emotional intelligence, leadership style, and organizational growth among employees in leadership roles across diverse sectors. Data is analysed using SPSS, applying reliability tests, correlation, and regression analyses to identify the strength of relationships between variables and test the hypotheses. Findings aim to offer actionable insights for integrating emotional intelligence and leadership development into organizational training programs, ultimately fostering a growth-oriented culture and enhancing overall performance. This research contributes to both academic knowledge and practical applications in leadership and organizational development.